PENGELOLAAN TANAH BENGKOK SEBAGAI HAK ASAL USUL SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA (STUDI KASUS DI KABUPATEN KUDUS) - Anggit Wicaksono; Dwiyana Achmad H (LPPM Universitas Pekalongan, 2016)
Villages Act requires a paradigm shift toward the village, which puts the village as a subject not related objects rural development within the framework of the Unitary Republic of Indonesia. One of the things that is being debated is related to the management of bengkok village land. Before the birth of the Village Act, bengkok village land is an asset village partly used to provide compensation / income for the village head and the village because of his so-called origin inherent rights because of the positions. With the Act the village, the village head and village get income fixed and allowances budgeted in APB village a source of funding is the revenue villages. Their fixed income and this additional polemical for the continuity of the village administration, because of the Law of the village is considered removing government authority bengkok village land to work the land as compensation for his position.